Factors Affecting Exclusive Breast Milk in Work Area of South Kluet Health Center in 2022: - Kiki Asrifa Dinen; Razia Begum Suroyo; Sarma Lumban Raja (Science Midwifery, 2022)
Breastfeeding is an important factor in the survival of the baby. Efforts to reduce infant mortality need special attention to infant health, from care at birth to proper feeding. Forknowing and analyzing the factors that influence exclusive breastfeeding in the Working Area of the South Kluet Health Center in 2022. This type of research uses quantitative research with research methods that are analytical surveys with a Cross Sectional approach. This research was conducted in the Working Area of the South Kluet Health Center in 2022. The population was 94 people with a total sampling technique of 94 respondents. Quantitative data analysis with univariate, bivariate and multivariate analysis. Results : Based onThe chi-square test was obtained at the cultural level variable p = 0.015, knowledge p = 0.001, attitude p = 0.018, husband support p = 0.009, birth attendant support p = 0.000, which indicates there are influencing factors. Conclusion: There is a relationship between culture, knowledge, attitudes, husband's support and birth attendant support for exclusive breastfeeding in the working area of the South Kluet Health Center in 2022, and of all the factors that influence exclusive breastfeeding, cultural factors are the most dominant influencing exclusive breastfeeding. with the value of Exp(B) 5,923.